2018
DOI: 10.1007/s00431-018-3230-y
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal screening in the Czech Republic: increased prevalence of selected diseases in low birthweight neonates

Abstract: Neonates with low birthweight (LBW) represent a vulnerable population. This retrospective study analyzed the birth frequency of diseases detected by neonatal screening (NBS) in normal and LBW neonates in the Czech Republic. Between years 2002 and 2016, the number of screened disorders in the Czech Republic gradually increased from two to 13. Prevalence of screened diseases was calculated for cohorts ranging from 777,100 to 1,277,283 neonates stratified by birthweight. Odds ratio of the association of LBW with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…9,10,[12][13][14]22,23 Studies of European, US, and Qatar populations have identified incidences similar to Asia and Australia. 3,10,[15][16][17][18][24][25][26][27][28] However, the Eastern and Jawf provinces of Saudi Arabia reported a much higher incidence (31.1 per 100,000), which is attributed to a high rate of consanguineous marriage and a founder effect. 29 In one study, patients identified by NBS generally had higher levels of enzyme activity and a higher overall long-chain fatty acid oxidation flux in cultured fibroblasts than those reported before NBS implementation.…”
Section: Epidemiology Of Faods By Country and Regionmentioning
confidence: 99%
“…9,10,[12][13][14]22,23 Studies of European, US, and Qatar populations have identified incidences similar to Asia and Australia. 3,10,[15][16][17][18][24][25][26][27][28] However, the Eastern and Jawf provinces of Saudi Arabia reported a much higher incidence (31.1 per 100,000), which is attributed to a high rate of consanguineous marriage and a founder effect. 29 In one study, patients identified by NBS generally had higher levels of enzyme activity and a higher overall long-chain fatty acid oxidation flux in cultured fibroblasts than those reported before NBS implementation.…”
Section: Epidemiology Of Faods By Country and Regionmentioning
confidence: 99%
“…PTB also has a significant influence on newborn CH. LBW, PTB, and GDM were confirmed to be associated with maternal exposure to air pollution, which may affect the occurrence of newborn CH indirectly (David et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pilot testing for SMA and SCID began in January 2022 in Prague and Moravia [ 735 ]. Recent research has focused on the epidemiology of diseases detected by NBS [ 736 ], with particular emphasis on low birthweight neonates [ 737 ] and the growth patterns associated with NBS-detected CAH [ 738 ]. A study of the way parents are informed about NBS and the variables associated with their awareness has resulted in several new educational measures including seminars for healthcare providers and the development and distribution of new educational materials [ 739 ].…”
Section: Resultsmentioning
confidence: 99%